Pengembangan LKPD Berbasis Kearifan Lokal Cerita Rakyat Bali “Kebo Iwa”: Analisis Kevalidan dan Kepraktisan pada Pembelajaran Bahasa Siswa Kelas 2 Sekolah Dasar - Aulia, Salsabila Risqi; Istiq’faroh, Nurul; Rizqiyah, Azmi Aliyatur (Innovations in Multidisciplinary Education Journal, 2026)
This study was motivated by elementary school students’ limited understanding of local wisdom and the scarcity of contextual teaching materials, particularly regarding listening skills. Learning that does not integrate local culture results in students being less familiar with the values in their environment and less actively engaged in the learning process. In fact, the integration of local wisdom into learning plays a crucial role in character development and enhances the meaningfulness of learning. This study aims to develop Student Worksheets (LKPD) based on local wisdom using the Balinese folktale “Kebo Iwa” and to determine their validity and practicality among second-grade elementary school students. This study employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of analyze, design, development, implementation, and evaluate. The research subjects were second-grade students at SDN Kandangan III. Data collection was conducted using expert validation sheets, teacher response questionnaires, and student response questionnaires. Data analysis employed quantitative descriptive analysis using Likert and Guttman scales to determine the product’s feasibility. The results indicated that the developed worksheets achieved a validity rate of 92%, classified as highly valid. The practicality rate, based on teacher responses, was 91%, and based on student responses, 86%, both falling into the highly practical category. These findings indicate that the LKPD based on local wisdom is suitable for use as teaching material in listening comprehension instruction for second-grade elementary school students. Thus, the development of this LKPD not only supports the improvement of listening skills but also contributes to instilling local cultural values and creating contextual and meaningful learning.